LEGAL EDUCATION ON THE TEACHER'S PROFESSION IN APPLY CONFLICT MANAGEMENT - Arista Candra Irawati; Anis Mashdurohatun Mashdurohatun; Adhi Budi Susilo (International Journal of Law Society Services, 2021)
The fact that occurs as a form of disciplining students so that they are more disciplined gets a dilemma with accusations of violence against students where parents do not directly compromise or solve problems but directly report to the police where the teacher is always the victim and the object of the sufferer. it is very ironic that the existence of a teacher as a hero without merit and from a science teacher is very weak. On the one hand, it must realize the goals of national education, on the other hand, in carrying out its authority it is considered to violate the law. This activity involved partners from the Semarang Regency Education, Culture, Youth and Sports Office. The problems faced by the first partner, Has the teaching profession in the district have implemented conflict management as a form of legal protection for the second teaching profession, What is the impact of conflict management legal counseling on the teaching profession in Semarang Regency. in handling and resolving conflicts The implementation of community service activities is carried out using a participatory approach method. meaning that the participants are required to actively participate during the activity. From the results of the first community service activities, the teaching profession in Semarang district does not understand conflict management as a legal protection in applying discipline to students so as not to have an impact on legal issues, secondly seeing the pre-test and post-test conducted on 36 participants marked by indicators of increasing knowledge participants on how to resolve conflicts between the teaching profession and students, as well as increasing knowledge about the application of the Law